DAMPAK PUBLIC RELATIONS DALAM MANAJEMEN KRISIS KEAMANAN DAN KESELAMATAN ANCAMAN TERORISME DI BANDAR UDARA INTERNASIONAL I GUSTI NGURAH RAI DENPASAR - Loreza, Ghannez Novaldi; Suardana, I Wayan; Sofia Wijaya, Ni Made (Jurnal IPTA (Industri Perjalanan Wisata); Vol 5 No 2 (2017): Jurnal IPTA (Desember 2017)DO - 10.24843/IPTA.2017.v05.i02.p04, 2018)
The aim of this research is to find out how does the public relations may involved in the security and safety crisis management of terrorism threat in  I Gusti Ngurah Rai International Airport of Denpasar, and how it may affect the image of the airport itself. Several informants were being interviewed and as much as 116 repondents gave their answers related to I Gusti Ngurah Rai International Airport of Denpasar’s image. This research use descriptive qualitative data analysis technique by collected the data, reductions, presented the results, and draw a conclusion. This research also use the triangulation data technique to ensure the informations given by the informants were valid. The results shown that security and safety crisis management in I Gusti Ngurah Rai International Airport of Denpasar has twice security check point, using the recent technology, corporate with the authorities, and do the silent investigation. The roles of public relations itself are planning the terrorism encounters training programme, make a positive image of the airport, and build communications during and after the crisis. I Gusti Ngurah Rai International Airport of Denpasar has a good image of security based on the result of the questioners. There was several issues in the applications of terrorism encounters in the airport such as, some of the check in counter agents didn’t ask the security questions to the passenger and the x-ray officer didn’t check the luggage thoroughly that caused Qatar Airways flight had to return to base in 2015.